The Practice of Burning Votive Paper in Vietnamese Buddhist Temples: A Study on the Spiritual Dimension and Buddhist Perspective - Nguyen Tran Tien, (Tạp chí Khoa học Xã hội và Nhân văn (VNU Journal of Social Sciences and Humanities), 2025)
Every year, the Vietnamese people reportedly burned thousands of tons of votive paper in the hope of pleasing the dead and getting spiritual peace in mind and material rewards. The discourses surrounding the practices lay great emphasis on burning votive offerings, or the excessive forms of this practice as superstitious. Findings from the study of burning votive paper in Vietnamese Buddhist Temples reveal that the practice has become associated with wastefulness, fire hazard, and environmental concerns. For this reason, the present study firstly traces the origins of votive paper burning of the ancient people. Secondly, the study focuses on its introduction into Vietnam as an act of worship in Vietnamese folk tradition and its current negative impacts. Finally, the author then tries to analyze based on Buddhist perception on life and death in order to reject this practice as its incompatibility with Buddhism. Despite the fact that a single case does not aim at generalization, research outcomes raises -some viewpoints of the relevant agencies on the practice of burning votive paper that contribute to the protection of the spiritual tradition and natural environment of Vietnam.Received 6 th December 2021; Revised 18 th February 2022; Accepted 17 t h March 2022